2004
DOI: 10.1080/13547500400024768
|View full text |Cite
|
Sign up to set email alerts
|

Systemic markers of the redox balance in chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is highly prevalent and its pathogenesis is still not completely clarified. Clinically stable patients (n=21) and healthy subjects (n=24) were studied for blood markers of oxidative injury and antioxidant status. The plasma concentration of protein carbonyls was significantly increased in COPD patients, both ex-smokers (0.76 +/- 0.28 nmol mg(-1)) and smokers (0.99 +/- 020 nmol mg(-1)) versus controls (0.49 +/- 0.14 nmol mg(-1)) . The concentration of total thiols wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 14 publications
3
45
0
Order By: Relevance
“…Our finding of lower GPX activity in patients with COPD than in healthy persons is in agreement with previous studies [19,26]. Interestingly, both animal and human studies suggest that antioxidant enzymes might play a role in pulmonary vascular physiology and pathology.…”
Section: Discussionsupporting
confidence: 95%
“…Our finding of lower GPX activity in patients with COPD than in healthy persons is in agreement with previous studies [19,26]. Interestingly, both animal and human studies suggest that antioxidant enzymes might play a role in pulmonary vascular physiology and pathology.…”
Section: Discussionsupporting
confidence: 95%
“…We found that serum TOS levels of COPD patients were significantly higher than those of control individuals. Santos et al 25 found that the plasma concentration of protein carbonyls was significantly increased in COPD patients compared to that in control individuals. The activity of antioxidant enzyme superoxide dismutase was increased in erythrocytes, while glutathione peroxidase activity was decreased in total blood.…”
Section: Discussionmentioning
confidence: 98%
“…5 Cigarette smoke also contains free radicals and induces oxidative DNA damage. 6 Oxidative DNA damage is thought to play a major role in carcinogenesis. 7 The level of 8-hydroxy-2 0 -deoxyguanosine (8-OH-dG), products of oxidative DNA damage, has been suggested to be a good indicator of oxidative stress in humans.…”
Section: Discussionmentioning
confidence: 99%